Nursing Reports: Annual Report Card 2021 - Richard Gray (MDPI AG, 2022)
As Editor-in-Chief of Nursing Reports, the focus of my work is to ensure submitted manuscripts are handled in a timely manner and that authors are provided with helpful and constructive feedback [...]